What drives FDI from non-traditional sources? A comparative analysis of the determinants of bilateral FDI flows - Maximiliano Sosa Andrés; Peter Nunnenkamp; Matthias Busse (Kiel Institute for the World Economy (IfW), 2012)
Non-traditional source countries of FDI play an increasingly important role, notably in developing host countries. This raises the question of whether the determinants of FDI differ systematically between traditional and non-traditional source countries. We perform Logit and Poisson Pseudo Maximum Likelihood estimations drawing on UNCTAD's database on bilateral FDI flows, including various emerging and developing countries as sources of FDI outflows. We find that economic geography variables are more relevant for FDI from non-traditional sources, while non-traditional investors appear to be as risk adverse as traditional investors. Access to raw materials represents a less important driving force of FDI from non-traditional sources. The differences are less pronounced for other types of FDI.
Keywords: F21; 330; FDI flows; types of FDI; source-host country pairs; location choices; gravity-type models; Direktinvestition; Entwicklungsländer-seitig; Schwellenländer-seitig; Standortwahl; Gravitationsmodell; Welt; Entwicklungsländer; Schwellenländer